Noblewomen, aristocracy and power in the twelfth-century Anglo-Norman realm - Johns, Susan M (2003)
This is the first study of noblewomen in twelfth-century England and Normandy, and of the ways in which they exercised power. It draws on a rich mix of evidence to offer an important reconceptualisation of women's role in aristocratic society, and in doing so suggests new ways of looking at lordship and the ruling elite in the high middle ages. The book considers a wide range of literary sources such as chronicles, charters, seals and governmental records to draw out a detailed picture of noblewomen in the twelfth-century Anglo-Norman realm. It asserts the importance of the life-cycle in determining the power of these aristocratic women, thereby demonstrating that the influence of gender on lordship was profound, complex and varied. This work will be of importance to specialists in history and medieval studies, as well as those interested in the experience of women and those working on lordship and feudalism.